Mycotic aneurysms due to Trichosporon asahii in a patient with ulcerative colitis under immunosuppression - Juan Luis Quintana; Xosse Carreras; Andrea S. Salcedo; Lourdes Torres Ruíz; Manuel Moreno Gonzales; Alfonso Del Castillo Mory; Hugo Cedrón Cheng; Alfredo Chiappe Gonzalez (IDCases, 2023)
Yeast fungi of the genus Trichosporon spp. can colonize the gastrointestinal tract in humans. In recent decades, the pathogenic role of Trichosporon asahii has been increasingly acknowledged especially in the setting of neutropenic patients with hematological malignancies. However, non-neutropenic patients who are immunosuppressed for other reasons are also at risk of developing invasive forms of this mycosis. We present the case of a 62-year-old male, with a history of ulcerative colitis under immunosuppressive treatment and previous exposure to antibiotics for various bacterial infections, who was admitted to the emergency department with a mycotic aneurysm of the abdominal aorta and left common iliac secondary to T. asahii infection. A multidisciplinary approach of the case (both early medical and surgical interventions) allowed the patient’s favorable outcome. The patient was followed for more than two years with no evidence of relapse. We postulate that the diagnosis of invasive Trichosporonosis should be considered in patients with inflammatory bowel disease (IBD) under immunosuppressive treatment and with prior exposure to antibiotics.